Examining undergraduate students' abstraction of conic sections in a dynamic geometry environment - Dintarini, Mayang; Fuad, Yusuf; Budiarto, Mega Teguh (Journal on Mathematics Education, 2024)
In solid geometry, the concept of conic sections plays an important role in teaching graphs such as parabolas, ellipses, and hyperbolas to undergraduate students in Mathematics Education. It is understood that the abstraction process in mastering conic sections is strongly needed. This study examines the abstraction process of conic sections among third-year undergraduate Mathematics Education students (4 males and 21 females) at Universitas Muhammadiyah Malang (UMM), Indonesia. The data was collected by analyzing students' responses in a 60-minute diagnostic test using the Abstraction in Context (AiC) framework. The test consists of 3 questions, validated by 2 Professors of UMM (average score = 4.14) and 2 lecturers (average score = 4.04). The results showed that 1 male and 11 female students did not reach the construction stage of AiC. Subsequently, a student with a low diagnostic test score and the least completion of AiC stages was observed further through an interview. This student passed through all stages of abstraction with the help of DGE. We also underscored undergraduates' challenges in this process, particularly in visualizing conic section objects, spatial thinking, and employing appropriate mathematical signs. Based on these findings, further research with a broader sample is needed to explore diverse abstraction processes.